2023
DOI: 10.3390/su151712825
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characteristics of the Household Carbon Footprint in an Aging Society

Ying Long,
Jiahao Feng,
Aolong Sun
et al.

Abstract: The aging population has posed a challenge to China’s carbon neutrality pledge. To study the household carbon footprint in an aging society, this paper has combined the age-specific consumption pattern and environmental input-output life cycle assessment (EIO-LCA) to calculate the carbon footprint of household consumption across age groups, and then identified the key pathways of carbon emissions via structural path analysis (SPA). Results indicate that the elderly contribute 11.65% to total consumption-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Also, transportation and mobile phone connectivity are indispensable services in urban areas. According to the study of Long et al, (2023) (40) and Bera et al, (2022) (41), the urban area's CF is significantly larger than that of rural areas. Conversely, the outcome went against the findings of Pang et al, (2020) (52), and Ottelin et al, (2019) (53), who found that urban households in Switzerland and Europe have lower direct emissions than rural households.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Also, transportation and mobile phone connectivity are indispensable services in urban areas. According to the study of Long et al, (2023) (40) and Bera et al, (2022) (41), the urban area's CF is significantly larger than that of rural areas. Conversely, the outcome went against the findings of Pang et al, (2020) (52), and Ottelin et al, (2019) (53), who found that urban households in Switzerland and Europe have lower direct emissions than rural households.…”
Section: Discussionmentioning
confidence: 98%
“…According to the researcher's viewpoint, the academic activities in nursing studies, such as printing, exams, and digital learning, combined with lifestyle choices, could have played a role in the rise of CF among the nursing students than the average CO2 emission per capita in EGYPT. Numerous studies found that the biggest contributor to CF was housing expenditure (Long et al, 2023 (40) , Bera et al, 2022 (41) , and Fahmy et al, 2022 (42) ).…”
Section: Discussionmentioning
confidence: 99%